A Short Communication on Progress and Problems of ITER Fusion Project (Bulletin of Pure and Applied Sciences – Physics, 2022)
In recent years, it becomes clear that ITER project in France, as one of the largest  experimental fusion reactors underway, is far away from achieving net energy  production. In this review article, we presented a short communication this week with  Robert Neil Boyd, a senior physicist who happens to have his own working design of  fusion reactor in the past. We hope that this transcript of our communication with him  (as per 15-17th Nov. 2021) may be found useful for younger scientists.